Armed violent conflict and healthcare-seeking behavior for maternal and child health in sub-Saharan Africa: A systematic review. - Gbadebo Collins Adeyanju; Pia Schrage; Rabiu Ibrahim Jalo; Liliana Abreu; Max Schaub (PLoS ONE)
Background Over 630 million women and children worldwide have been displaced by conflict or live dangerously close to conflict zones. While the adverse effects of physical destruction on healthcare delivery are relatively well understood, the effects on healthcare-seeking behavior remain underexplored, particularly in sub-Saharan Africa. This study aims to better understand the interconnections and knowledge gaps between exposure to armed violent conflicts and healthcare-seeking behaviors for maternal and child health in sub-Saharan Africa. Methods Five key electronic databases (PubMed, Scopus, Web of Science, PsycNET, and African Journals Online) were searched for peer-reviewed publications between 2000 and 2022. The review was designed according to PRISMA-P statement and the protocol was registered with PROSPERO database. The methodological quality and risks of bias were appraised using GRADE. A data extraction instrument was modelled along the Cochrane Handbook for Systematic Reviews and the Centre for Reviews and Dissemination of Systematic Reviews. Result The search results yielded 1,148 publications. Only twenty-one studies met the eligibility criteria, reporting healthcare-seeking behaviors for maternal and child health. Of the twenty-one studies, seventeen (81.0%) reported maternal health behaviors such as antenatal care, skilled birth attendance, postnatal care services, and family planning. Nine studies (42.8%) observed behaviors for child health such as vaccination uptake, case management for pneumonia, diarrhea, malnutrition, and cough. While conflict exposure is generally associated with less favorable healthcare-seeking behaviors, some of the studies found improved health outcomes. Marital status, male partner attitudes, education, income and poverty levels were associated with healthcare-seeking behavior. Conclusion There is a need for multifaceted interventions to mitigate the impact of armed violent conflict on healthcare-seeking behavior, given its overall negative effects on child and maternal healthcare utilization. While armed violent conflict disproportionately affects children's health compared to maternal health, it is noteworthy that exposure to such conflicts may inadvertently also lead to positive outcomes. Prospero registration number CRD42023484004.